Analisis Tantangan dan Peluang Penggunaan Artificial Intelegence Pada Mahasiswa Teknologi Informasi: Pendekatan K-Means Clustering - Ali, Nur; Kusumodestoni, R. Hadapiningradja; Wibowo, Gentur Wahyu Nyipto (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the perceptions, challenges, and opportunities of Information Technology students in utilizing Artificial Intelligence (AI) in the learning process. Using a quantitative approach with the K-Means Clustering method, this study groups students based on their level of knowledge and utilization of AI. The results indicate two main profiles: students with high AI literacy but moderate utilization, and students with low understanding but intensive utilization. The second group faces similar challenges but views AI opportunities differently. These findings highlight the importance of user profile-based learning strategies to create an adaptive and sustainable AI ecosystem. This research contributes to the development of higher education policy.